PENGABDIAN PADA MASYARAKAT MELALUI KULIAH KERJA MAHASISWA (KKM) DI KELURAHAN BULAKAN KECAMATAN CIBEBER KOTA CILEGON - Rani Sri Sumarsih; Slamet Gunadi; Fatari Fatari; Iqbal Budianto; Reni Asmara Dewanti; Devia Ervinah Putri (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Based on Law No. 12 of 2012 defines community service as one of the activities of the academic community by utilizing Science and Technology to educate the nation's life and improve people's welfare. The implementation method for community service activities (PkM) currently focuses more on implementing work programs that have been systematically arranged. Carried out by KKM Group 75 Students and Field Supervisors and Associate Lecturers by going directly to the field to visit the community and data sources needed for questioning through direct interviews both personally and organizationally or data sources obtained through the sub-district office or office subdistrict. The data in this activity comes from primary and secondary data. The primary data is Bina Bangsa University Student Work Class students, namely group of 75 students consisting of 14 members plus one Field Supervisor (DPL) and three Associate Lecturers. The series of activities that have been carried out by the 75 group Student Work Lecture participants are concentrated in several work programs that have been determined by the Bina Bangsa University College. The conclusion is to provide opportunities for students to be able to transform their knowledge to the community in terms of understanding hygiene, health and a healthy lifestyle. make a wider contribution to society through MSME assistance and the creative economy in terms of developing online promotions and marketing so that income can increase, and collaboration between lecturers and students in community service can overcome problems faced by the community